ANALISIS HUBUNGAN BIAYA PROMOSI DENGAN PENDAPATAN PADA PT. BANK XYZ - Wulansari, Murwani; Azlina, Yunidyawati (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This study aims to determine and analyze the effect of promotion costs on income at PT. Bank XYZ. The study was conducted by linear regression that was processed by means of statistical program SPSS16.00. The analysis shows the regression equation as follows: Y = -162982.754 + 247.964X. The result of research shows that there is influence between variable X that is promotion cost with variable Y that is income. However, the effectis not significant because the p-value 0.216 is greater than the 0.05 significance level. Keywords: biaya promosi, penjualan